(untitled) (International Journal of Business, Economics and Management, 2019)
Advancements in technology have a massive impact on the workplace including recruitment of staff. The aim of this study was to examine jobseekers’ behavior towards e-recruitment system usage by jobseekers in Malaysia. The study population was jobseekers intending to apply for jobs in the advertising industry. This was a quantitative study and self-administered questionnaires were used to collect information from a sample of 100 jobseekers. The SPSS statistical tool was used to generate descriptive statistics and inferential statistics. The results revealed that perceived usefulness was the key determinant of e-recruitment adoption. However, the impact of perceived information content quality (PICQ) and perceived search engine optimization (PSEO) was insignificant. The implications of this study are that recruitment agencies and human resources practitioners need to focus on the perceived usefulness of the e-recruitment system to attract and create the desire in jobseekers to use e-recruitment system.